Physical compatibility of insecticides and fungicides and their phytotoxicity on castor: Physical compatibility of insecticides and fungicides and their phytotoxicity on castor - G MADHURI,; P DURAIMURUGAN,; V DIVYA RANI,; K SADAIAH,; G NEELIMA,; M RAJASHEKAR,; CH V DURGA RANI,; G ANURADHA,; M VENKATA RAMANA, (Journal of Oilseeds Research, 2020)
All 18 combinations of insecticides and fungicides tested were physically compatible. The combinations viz.,novaluron + carbendazim, acetamiprid + carbendazim, acetamiprid + carbendazim 12% + mancozeb 63% andbuprofezin + carbendazim 12% + mancozeb 63% showed phytotoxic symptoms like vein clearing and scorching onleaves, remaining all other treatment combinations were compatible.